2010
DOI: 10.1136/emj.2009.085019
|View full text |Cite
|
Sign up to set email alerts
|

The use of propofol for procedural sedation and analgesia in the emergency department: a comparison with midazolam

Abstract: Both propofol and midazolam given at the recommended doses were equally safe and effective for PSA in the ED. The propofol group was discharged much earlier than to the midazolam group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…5,6,9 41 The most common indications for procedural sedation were orthopedic manipulation, abscess incision and drainage, and direct current cardioversion. Most trials included patients with a mean or median age of approximately 20-57 years, 9,10,12 17,19 22,24 26,28,31 34,37 41 weight of approximately 60-85 kg, 10,12 15,19,20,22,34,37,41 and American Society of Anesthesiologists classification 1 or 2 (defined as patient is completely healthy and fit or patient has mild systemic disease). 11 …”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,9 41 The most common indications for procedural sedation were orthopedic manipulation, abscess incision and drainage, and direct current cardioversion. Most trials included patients with a mean or median age of approximately 20-57 years, 9,10,12 17,19 22,24 26,28,31 34,37 41 weight of approximately 60-85 kg, 10,12 15,19,20,22,34,37,41 and American Society of Anesthesiologists classification 1 or 2 (defined as patient is completely healthy and fit or patient has mild systemic disease). 11 …”
Section: Data Synthesismentioning
confidence: 99%
“…Most trials included patients with a mean or median age of approximately 20-57 years, 9,10,12 17,19 22,24 26,28,31 34,37 41 weight of approximately 60-85 kg, 10,12 15,19,20,22,34,37,41 and American Society of Anesthesiologists classification 1 or 2 (defined as patient is completely healthy and fit or patient has mild systemic disease). 11 17,19 21,28,30 Details on specific groups of participants who were included and excluded in each study can be found in Tables 1 and 2. Total doses of propofol ranged from 0.75 to 1.86 mg/kg, 10 15,21,22,25,26,31 36,40,41 with the most common dosing regimen being a 1.0-mg/kg bolus followed by 0.5 mg/kg every 3 minutes as needed for additional sedation.…”
Section: Data Synthesismentioning
confidence: 99%
“…We also evaluated patient opinion of the procedure to assess for tolerability of the interventions. To validate the above models, we reported the P value of the Le Cessie-van Houwelingen test, [14,15] and assessed for the effect of collinearity using the variance inflation factors (VIFs). A VIF of greater than five was considered a priori an unacceptable level of dependency between the candidate predictors.…”
Section: Methodsmentioning
confidence: 99%
“…However, further studies are needed in order to evaluate the antinociceptive effect of ayahuasca in the presence and absence of antagonists to better elucidate its mechanism of action. Ayahuasca interactions with propofol in the antinociceptive tests were not evaluated because the analgesic effect after propofol acute administration is too short (Anwar, Abdel-Rahman, 1998;Rahman, Hashim, 2011).…”
Section: Treatment and Doses (Mg/kg)mentioning
confidence: 99%